Analysis of fatigue among public bus driver in Kuantan - Nik Nurul Fathihah, Nik Azman (2018)
This study deals with the analysis of fatigue among public bus driver in Kuantan that becomes one of the concerned risk factors that could lead to accident involvement. The number of road accidents gains much attention through these years due to significant increase year after year. The other types of vehicles also shows an increase and decrease in rate of road accidents occurrence, however the most worrying thing is that road accidents involving buses. Buses accident usually involving the biggest number of injuries and deaths compared to the other vehicle. The objective of this research to investigate the relationship between high level of fatigue among bus driver and crash involvement and also to investigate the risk factors in the bus driver schedule that could impact the level of fatigue among public bus driver. It begins with the main focus of this research which is analysis of fatigue among public bus driver in Kuantan. Fatigue is one of the parameter that acts as a sign of declination of bus driver’s performance. Another parameter such as sleepiness, driving’s discipline and driving skills were not being studied in this research. The findings of this study proved that high fatigue level do contributes to accident involvement. The risk factors such as long period of driving, driving at night, irregular schedule and associated of other workload during driving do cause the high level of fatigue. However, split schedule does not cause high level of fatigue. Demographic factors such as age, gender also are proven does not lead to high level of fatigue. While smoking habit do cause high level of fatigue. Another risk factor that has been studied which is work environment, which are proven does not lead to high level of fatigue. All of the data collection was conducted through questionnaire, document interview, observation and walkthrough survey. Due to the confidentiality issues, document review process is limited and only the name list of bus drivers can be reviewed. Then the data obtained were analysed by two different methods; which is Statistical Package for Social Science (SPSS) software and Fatigue Index Calculator (FIC) in order to analyse the relationship between each observed risk factors and fatigue level.